Peran Bimbingan dan Konseling Islam dalam Meningkatkan Moral Remaja - Salsabila, Suci; Junia Vitaloka, Viola (Yayasan Darussalam Bengkulu, 2023)
The aim of this research is to shape and improve the morals of teenagers through Islamic-based counseling. This research was conducted in the city of Bengkulu, because in the city of Bengkulu the morals of teenagers are still very worrying. Data collection techniques use qualitative research carried out through observation, interviews and field research. This research also uses informant identification which will be carried out using a purposive sampling technique, namely identifying informants based on certain criteria.